Psychological responses to drought in northeastern Brazil - Coêlho, Angela E. L.; Adair, John G.; Mocellin, Jane S.P. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This study of cumulative effects of drought in Northeast Brazil assessed the psychological responses (anxiety, emotional distress, and PTSD) of 102 individuals living in a city (Queimadas) in a drought-prone area compared to the responses of 102 persons living in a drought-free control city (Areia) of comparable size. As predicted, the findings revealed that residents in the drought area (Queimadas) had significantly higher levels of anxiety and emotional distress than residents in the no-drought area (Areia). In the drought area, women had significantly higher levels of anxiety and men had significantly higher levels of emotional distress than women and men, respectively, in the no-drought area. Likely because of their role vulnerability, women had significantly higher levels of anxiety and emotional distress than men. As predicted, Post-traumatic Stress Disorder (PTSD) was unrelated to the drought. Although descriptive, the results provide baseline data for comparisons as the drought deepens and offer insights and suggestions for further research into the psychological consequences of drought.